Factors associated with pruritus uremic in chronic kidney failure patients - Harlim, Ago (Journal of Pakistan Association of Dermatologists, 2020)
Objective Uremic pruritus is one of the most distressing symptoms in patients with chronic renal failure. Interestingly, pruritus is not typically found in acute renal failure. Etiology and pathogenesis of uremic pruritus remain unclear. Several studies have demonstrated controversial results. Our study evaluated the frequency and intensity of uremic pruritus in patients with chronic renal failure (CRF) on hemodialysis including its associated factors. The aim of our study was to determine etiology and pathogenesis of uremic pruritus. Â Methods The study was a cross-sectional study conducted at Dr. Kariadi Hospital in Semarang city involving 33 hemodialysis patients between June and November 2005. About 6 cc of blood volume was withdrawn from each patient before the patient undergoing hemodialysis. Laboratory findings including blood urea, parathyroid hormone, calcium, phosphate, magnesium, vitamin A, and interleukin 2 levels were evaluated. Patient were be interviewed and examined if they had other diseases that may also cause pruritus. Â Results Uremic pruritus was found in 75.8% of the patients. Uremic pruritus had no correlation with urea level; secondary hyperparathyroidism, elevated divalent cations levels such as calcium, phosphate, magnesium levels as well as with hypervitaminosis A, interleukin-2 level or any group of those variables. On the other hand, uremic pruritus correlated to concomitant diseases. The intensity of uremic pruritus was related to the duration of hemodialysis. Â Conclusion Multifactorial facets could be involved in the pathogenesis of uremic pruritus. Further experiments are required to reveal greater details regarding the pathogenesis of uremic pruritus. Â